Minimizing environmental risks to progress the marine renewable energy industry (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As the marine renewable energy (MRE) industry continues to expand worldwide, challenges remain to consent projects. Deployment and consenting barriers of MRE devices are primarily due to insufficient information on the potential effects on marine animals, habitats, or ecosystem processes. Since 2010, Ocean Energy Systems (OES)-Environmental, an initiative under the International Energy Agency Ocean Energy Systems, has assessed what is known about the environmental effects of MRE and developed approaches to facilitate consenting. OES-Environmental’s goal is to mobilize information and international practitioners to coordinate scientific research that helps the industry progress in an environmentally responsible manner. As such, OES-Environmental has categorized risks to the environment from MRE devices as stressor-receptor interactions, where stressors are the devices or other parts of the associated systems that may cause stress, injury, or death to receptors such as marine animals, habitats, and ecosystem processes. As of 2025, four stressor-receptor interactions are considered to be retired (i.e., risks that are unlikely to cause harm to receptors and need not be fully investigated for every project) for a small number of devices (one to six), based on available scientific literature and environmental monitoring: changes in oceanographic systems, changes in habitat, underwater noise, and electromagnetic fields. Other interactions have been deemed to lack sufficient information to be retired: entanglement, displacement, and collision risk. Collision risk remains the main barrier to consenting new tidal and riverine energy projects. As limited grid-scale MRE deployments and the difficulties of field monitoring in high-energy environments restrict our understanding of some of these interactions, OES-Environmental is also evaluating the potential environmental effects of MRE at different scales, as well as assessing the applicability of integrative approaches to increase the environmental acceptability of MRE devices. While most MRE projects have focused on generating power at grid scale for regional or national electricity systems, numerous valuable and profitable off-grid or micro-grid applications exist. These include powering offshore aquaculture, ocean observation systems, and remote communities. Such applications will require the use of smaller devices, which are expected to have different or potentially lower environmental effects compared to grid-scale systems. To help the MRE industry progress, there is also a need to make sure that devices minimize harm to the environment from their design phase. Improving the environmental acceptability of MRE devices involves effectively using natural resources, minimizing environmental risks, adhering to the relevant regulations, and generating potential benefits. Regardless of the device archetype and geographic location, environmental acceptability will facilitate consenting processes and deployment. As the MRE industry targets new off-grid market applications, moves towards large-scale arrays of devices, and expands to more diverse locations like tropical and subtropical regions, the benefits and risks of a particular device, system, or array could be used as valuable design drivers.